Aerodynamic design of separate-jet exhausts for future civil aero-engines, Part II: design space exploration, surrogate modeling, and optimization - Goulos, Ioannis; Otter, John J.; Stankowski, Tomaz; MacManus, David G.; Grech, Nicholas; Sheaf, Christopher T. (American Society of Mechanical Engineers (ASME), 2016)
The aerodynamic performance of the bypass exhaust system is key to the success of future civil turbofan engines. This is due to current design trends in civil aviation dictating continuous improvement in propulsive efficiency by reducing specific thrust and increasing bypass ratio (BPR). This paper aims to develop an integrated framework targeting the automatic design optimization of separate-jet exhaust systems for future aero-engine architectures. The core method of the proposed approach is based on a standalone exhaust design tool comprising modules for cycle analysis, geometry parameterization, mesh generation, and Reynolds-averaged Navier–Stokes (RANS) flow solution. A comprehensive optimization strategy has been structured comprising design space exploration (DSE), response surface modeling (RSM) algorithms, as well as state-of-the-art global/genetic optimization methods. The overall framework has been deployed to optimize the aerodynamic design of two civil aero-engines with separate-jet exhausts, representative of current and future engine architectures, respectively. A set of optimum exhaust designs have been obtained for each investigated engine and subsequently compared against their reciprocal baselines established using the current industry practice in terms of exhaust design. The obtained results indicate that the optimization could lead to designs with significant increase in net propulsive force, compared to their respective notional baselines. It is shown that the developed approach is implicitly able to identify and mitigate undesirable flow-features that may compromise the aerodynamic performance of the exhaust system. The proposed method enables the aerodynamic design of optimum separate-jet exhaust systems for a user-specified engine cycle, using only a limited set of standard nozzle design variables. Furthermore, it enables to quantify, correlate, and understand the aerodynamic behavior of any separate-jet exhaust system for any specified engine architecture. Hence, the overall framework constitutes an enabling technology toward the design of optimally configured exhaust systems, consequently leading to increased overall engine thrust and reduced specific fuel consumption (SFC).
Keywords: Aerodynamics; Aerospace; Aerospace applications; Aerothermodynamics; Computational fluid dynamics; Design optimization; Propulsion systems